Challenges of managing and preserving audio-visual archives in archival institutions in Sub Saharan Africa: a literature review. (16th July 2020) - Rakemane, Donald; Mosweu, Olefhile
Abstract : Purpose: The purpose of this paper is to identify challenges related to the management and preservation of audio-visual (AV) records and/or archives in archival institutions in Sub Saharan Africa and suggests strategies for resolving them. Design/methodology/approach: This study is qualitative in nature and used content analysis from desk top review of literature to identify the challenges and suggested solutions. Findings: Among others, the study revealed that budgetary constraints, poor environmental controls, ill-equipped staff and technological obsolescence are the major challenges hampering the efforts of archival institutions in Sub Saharan Africa to manage and preserve AV archives. Research limitations/implications: The contextual differences due to existing political set ups in archival agencies in Sub Saharan Africa may or may not be receptive to some of the strategies suggested for the improvement of managing and preserving audio visual archives. Practical implications: The paper provides practical solutions which can inform policy and practice; thus, if adopted by archival agencies, the findings can add to improvements in the management and preservation of AV records. Originality/value: The study contributes to the body of knowledge on the preservation and management of AV archives in the context of Sub Saharan Africa.